The Effect of Social Media Marketing and Electronic Word of Mouth (E-WOM) on Purchasing Decisions: The Mediating Role of Purchase Intention - Icha Tri Pratiwi; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (International Journal of Management, Economic and Accounting, 2026)
Advances in information technology have driven rapid business transformation, leading to the emergence of many small and medium-sized enterprises (SMEs) and startups that are leveraging digital channels to expand their operations. This study aims to analyze the effect of social media marketing and electronic word of mouth on purchase decisions through purchase intention among consumers of KopiKuni Medan. The rapid development of digital technology and the increasing use of social media have encouraged businesses to optimize digital-based marketing strategies to attract consumers and enhance purchase decisions. This study employs a quantitative approach using a survey method. The sample was determined using purposive sampling, with a total of 230 respondents who are consumers of KopiKuni Medan. The data analysis method used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that social media marketing has a positive and significant effect on purchase intention and purchase decisions. Electronic word of mouth also has a positive and significant effect on purchase intention and purchase decisions. Furthermore, purchase intention has a positive and significant effect on purchase decisions. The indirect effect testing indicates that purchase intention is able to mediate the relationship between social media marketing and electronic word of mouth on purchase decisions significantly. These findings indicate that effective social media marketing strategies and positive, informative online consumer reviews can increase purchase intention, which ultimately leads to higher purchase decisions. The implications of this study highlight the importance for KopiKuni Medan to optimize social media content, enhance interaction with consumers, and encourage positive electronic word of mouth in order to improve competitiveness and business sustainability in the competitive culinary industry.